STRUKTUR MODAL PERUSAHAAN ROKOK DI INDONESIA - Handayani, Anita (Universitas Nahdlatul Ulama Surabaya, 2020)
The company's funding policy is a policy regarding the use of funds both using funds from internal and external funds. This funding policy needs to be implemented by both public and private companies. Capital structure decision is very important for public companies, because it can directly affect the company's finances. This research was conducted at cigarette industry companies that listed on the Indonesian Stock Exchange. This study is to analyze the factors that can affect the capital structure of cigarette companies in Indonesia..